Highly efficient micro-meso acidic H-USY catalyst for one step conversion of wheat straw to ethyl levulinate (biofuel additive) - Heda, Jidnyasa; Niphadkar, Prashant; Mudliar, Sandeep; Bokade, Vijay (Microporous and Mesoporous Materials, 2020)
Ethyl Levulinate (EL), biofuel additive can blend up to 20% with biodiesel to improve its fuel properties. Till the date, there are reports on homogeneous catalysts (H2SO4, ionic liquid) for synthesis of EL from raw biomass like wheat straw. To best of our knowledge, there is no single report on heterogeneous catalyst for one step synthesis of EL directly from wheat straw. This work is a successful attempt to use heterogeneous micro-meso acidic H-USY (post dealumination and desilication) for direct one step conversion of wheat straw to EL with higher EL yield 24.5 wt%, which is probably the highest so far.
Keywords: Acidity; ethyl levulinate; H-USY; Micro-meso; Wheat straw